Consideraţii cu privire la implicaţiile constituţionale ale aderării României la Uniunea Europeană - Aurel Ciobanu-Dordea (Romanian Journal of European Affairs, 2001)
By creating the European Union, the constitutive states gave a strong political dimension to the European Communities, transferring the exercise of competences until then strictly developed at the national level. The transfer has been irreversible and it involved a growing number of competences that set the basis of a new judicial order, a monist one. This is the new community judicial order, which incorporates the national judicial orders of those states and presents a number of specific characteristics (elaborated upon section 1). In order to respect the assumed commitments and to take into account their consequences, the member states operated changes of their national constitutional frameworks, the most significant aspects of those being worth to be presented (in section 2). Finally, since the establishment of these organizations, an enormous patrimony of rules, practices and evaluations regarding the European Union’s and member states’ fundaments of the political and judicial system has been accumulated. Romania must take into account the implications of the acquis communautaire (see section 3), like any other candidate country to the European Union.